Utilization of Digital Forensics in Proving the Crime of Disseminating Indecent Videos Through Facebook Social Media in the Legal Area of West Kalimantan Police - Awaka, M Qahar; Alhadiansyah, Alhadiansyah (JURNAL HUKUM SEHASEN, 2023)
The research entitled: "Utilization of Digital Forensics in Proving the Crime of Disseminating Indecent Videos Through Facebook Social Media in the KALBAR Police Legal Area" aims to find out and describe the implementation of information and research results in Pontianak city and to find out and analyze the utilization of digital forensics in proving the crime of spreading indecent videos through Facebook social media in the KALBAR police jurisdiction. This research was conducted using a sociological juridical approach method, namely examining and processing data from field research by starting from normative legal aspects supported by documents related to the problem in the form of regulations and cases related to the subject matter Based on research and data analysis, information can be obtained that the implementation of Digital Forensics related to the criminal act of spreading immoral videos through Facebook social media is a process of investigating and analyzing digital evidence related to the crime. In this case, the digital evidence that is the focus is an immoral video that spreads through the Facebook social media platform. Discussed in several important topics, namely; 1. The Role of Digital Forensics Related to the Crime of Dissemination of Indecent Video Through Facebook Social Media, 2. What Factors Become Obstacles in Proof Through Digital Forensics Related to the Crime of Dissemination of Indecent Video Through Facebook Social Media, 3. What Efforts Have Been Made in Optimizing Digital Forensic Evidence Related to the Crime of Immoral Video Dissemination Through Facebook. The conclusion that can be conveyed in this research is that the application of digital forensics involves several important stages, including the identification of digital evidence, storage of digital evidence, analysis of digital evidence, and presentation of findings. Digital forensics has a crucial role in proving legal cases. In Indonesia, the evidentiary system requires a minimum of two valid pieces of evidence and the conviction of the Judge to determine the guilt of the defendant. In the case of cyber crime, electronic evidence must meet both formal and material requirements to be considered valid and admissible in court. Therefore, the application of digital forensics in the investigation of cyber crime, especially the distribution of immoral videos, has an important role in finding relevant electronic evidence and evidence for the judicial process.